Dementia knowledge and attitudes of healthcare staff: A community hospitals’ perspective - Weiyao Han; Jia Hua Low; Gabriel Gerard Wenjun Yee; Catherine Qiu Hua Chan; Lian Leng Low (Proceedings of Singapore Healthcare)
Background As the global population ages, the prevalence of dementia increases, and the need for healthcare services increases. Healthcare workers should possess necessary knowledge and appropriate attitudes to care for dementia patients. Objectives There is a lack of studies of dementia knowledge and attitudes of healthcare workers in post-acute and intermediate care settings. Our study aims to address this gap and evaluate factors associated with dementia knowledge and attitudes in community hospitals. Methods Eligible healthcare workers from three community hospitals in Singapore were invited to fill in anonymous, self-administered questionnaires consisting of sociodemographic, work or training-related, assessment of self-competence factors together with Dementia Knowledge Assessment Scale (DKAS) and Approaches to Dementia Questionnaire (ADQ). Univariate analysis followed by multiple linear regression was conducted to determine the association between covariates with DKAS and ADQ scores. Results A total of 500 responses were obtained, giving a response rate of 60.2%. Mean DKAS and ADQ scores were 27.8 and 68.4 respectively. Multiple linear regression revealed better dementia knowledge was associated with occupation, highest education level, having attended a dementia training course, experience in caring for dementia patients and self-assessment of dementia knowledge. More positive attitudes towards dementia care were associated with occupation, time spent providing dementia care and self-assessment of attitude towards dementia care. Conclusion Healthcare workers in community hospitals exhibit positive attitudes towards providing dementia care but have a lower level of dementia knowledge compared to other study populations. Modifiable factors can be targeted to improve dementia knowledge and attitudes amongst healthcare workers.